Population-based screening for pulmonary tuberculosis utilizing community health workers in Ethiopia - Yared Merid; Yimtubezinash Woldeamanuel Mulate; Mesay Hailu; Tsegaye Hailu; Getnet Habtamu; Markos Abebe; Daniel G. Datiko; Abraham Aseffa (International Journal of Infectious Diseases, 2019)
Objective: To evaluate the utility of a volunteer health development army in conducting population screening for active tuberculosis (TB) in a rural community in southern Ethiopia. Methods: A population-based cross-sectional survey was conducted in six kebeles (the lowest administrative units). Volunteer women community workers led a symptom screening programme to identify adults ≥15 years of age with TB in the community. Individuals with a cough for ≥2 weeks had spot and morning sputum samples taken, which were examined using acid-fast bacillus (AFB) smear microscopy, culture, and Xpert MTB/RIF. Results: All 24 517 adults in the study area had a symptom screen performed; 544 (2.2%) had had a cough for ≥2 weeks. Among those with a positive symptom screen, 13 (2.4%) were positive on sputum AFB smear microscopy, 13 (2.4%) had a positive culture, and 32 (5.8%) had a positive Xpert MTB/RIF test. Overall, 34 TB cases (6%) were identified by culture and/or Xpert, corresponding to a prevalence of 139 per 100 000 persons. Conclusions: This study demonstrated the capability of community health workers (volunteer and paid) to rapidly conduct a large-scale population TB screening evaluation and highlight the high yield of such a programme in detecting previously undiagnosed cases when combined with Xpert MTB/RIF testing. This could be a model to implement in other similar settings. Keywords: Community TB, Prevalence, Health development army, Ethiopia